PENGARUH LATIHAN IMAGERY TERHADAP KETEPATAN SHOOTING FUTSAL - Muhamad Khalid Yusup; Firman Aditiyatama; Muh Ikhwan Iskandar (STKIP Muhammadiyah Kuningan, 2019)
This study aims to determine the effect of mental imagery training on shooting accuracy in men's futsal extracurricular at SMK Negeri 3 Kuningan. This type of research is an experiment with the design